LYRIC POEM IS «SEPTEMBER» OF IVAN IRLYAVSKY - Rebryk, N. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article analyzes the poem “September”, written by little-known Transcarpathian poet Ivan Irlyavskiy (Ivan Roshko). For the first time to the literature studies is introduced artistic and scientific material that reveals not only the creative work of this writer, but also contribute to understanding the literary life of Transcarpathia.